2018
DOI: 10.12973/iji.2018.11232a
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback, Spoken Accuracy and Fluency, and the Trade-off Hypothesis

Abstract: The current study was an attempt to investigate the effects of different corrective feedback (CF) conditions on Iranian EFL learners' spoken accuracy and fluency (AF) and the trade-off between them. Consequently, four pre-intermediate intact classes were randomly selected as the control, delayed explicit metalinguistic CF, extensive recast, and intensive recast groups. All participants took part in spoken reproduction tasks for six sessions and their spoken grammatical errors were treated differently. Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…For example, consistent prioritization of fluency might lead to over-lexicalized performance and fossilized learner interlanguage, which may be difficult to change. By contrast, consistent prioritization of accuracy might lead to a lack of fluency (Chehr Azad et al, 2018).…”
Section: A Revisit Of Oral Accuracy and Fluency In Fl Learningmentioning
confidence: 96%
“…For example, consistent prioritization of fluency might lead to over-lexicalized performance and fossilized learner interlanguage, which may be difficult to change. By contrast, consistent prioritization of accuracy might lead to a lack of fluency (Chehr Azad et al, 2018).…”
Section: A Revisit Of Oral Accuracy and Fluency In Fl Learningmentioning
confidence: 96%
“…The concern of feedback as a source of students' anxiety has also been reported as the reason for teachers' reluctance in giving feedback elsewhere (e.g., Kartchava et al, 2020;Roothooft & Breeze, 2016). As for the accuracy-fluency trade-off, concern has been grounded in the hypothesis of learners' limited attentional capacity (see Skehan, 1998, for an example); however, empirical research in the field of ELT, such as that by Azad et al (2018), has revealed that feedback does not necessarily result in the reduction of fluency. Additionally, teachers' lack of belief in the efficacy of feedback on pronunciation at lower English levels hereby was not well supported by findings of previous studies.…”
Section: Research Question 2: How Do Efl Vietnamese Teachers Give Fee...mentioning
confidence: 99%